Community-led approaches to research governance: a scoping review of strategies - Emily Doerksen; Alize E. Gunay; Scott D. Neufeld; Phoebe Friesen (Research Ethics Review)
Around the world, a growing number of communities are voicing their demands for authority in the governance of research involving them. Many such communities have experienced histories of exploitative, stigmatizing, intrusive research that failed to benefit them. To better understand what strategies communities are developing in order to have a say in research oversight, we conducted a scoping review of the international peer-reviewed and grey literature. Three primary strategies were identified: (1) guidelines; (2) community review boards; and (3) community advisory boards. Guidelines include documents developed by, with, or for communities to outline ethical behavior or conduct in research with or within the community. Community review boards offer ethical review of research protocols, much like traditional research ethics boards, but are community led and focus on community interests. Community advisory boards consist of representatives from a given community and are developed to advise institutions or research teams on community-level ethical matters pertaining to research projects. Initiatives led by Indigenous communities far outnumbered others in the sample, reflecting the legacy of continuous Indigenous resistance to research as a tool of colonialism. In several cases, communities in marginalized neighbourhoods, where harmful and exploitative research practices have taken place, emphasized the significance of community-led governance grounded in shared geographical and social contexts. We discuss some of the beneficial and challenging features of each type of strategy and offer recommendations for stakeholders who wish to support community-led efforts in research ethics.